Rethinking Criminal Liability of Beneficial Owners in Tax Crime Enforcement - Nopriyandi Nopriyandi; Amad Sudiro; Hery Firmansyah (Contrarius Indonesia, 2026)
The development of the global economy and the increasing complexity of corporate ownership structures have created significant challenges in enforcing tax crime regulations. Ownership arrangements involving multiple intermediary entities often enable beneficial owners to conceal their identities, raising questions regarding whether criminal liability can effectively be attributed to the beneficial owner. This study aims, first, to analyze the legal construction of criminal liability of beneficial owners in tax crimes in Indonesia. Second, it seeks to identify weaknesses in the enforcement of criminal liability against beneficial owners in tax-related offenses. Third, the study proposes a reconstructed legal policy model that positions the beneficial owner as a subject who can be held criminally liable. This research employs a normative legal research method with primary approaches consisting of statutory, conceptual, and comparative analyses. The sources of data consist of primary legal materials and secondary legal materials. First, the complexity of corporate ownership structures highlights the importance of the beneficial owner concept in identifying individuals who ultimately control and derive economic benefits from corporations, although Indonesian regulations have not yet explicitly linked this concept to criminal liability in tax law enforcement. Second, law enforcement efforts continue to encounter obstacles due to regulatory frameworks and evidentiary systems that remain largely formalistic and focus primarily on administrative subjects, thereby making it difficult to reach the substantive actors behind corporate structures. Third, a reconstruction of the legal framework is required through regulatory reform, enhanced transparency of ownership structures, and the integration of registration systems along with stronger institutional coordination to effectively hold beneficial owners accountable.